MON-214 Biochemical Abnormalities in Endocrine Function Associated with Lutetium 177-DOTATATE Therapy in Metastatic Pheochromocytoma and Paraganglioma - Gubbi, Sriram (J Endocr Soc, 2020)
Background: Lutetium-177 ((177)Lu) DOTATATE (Lutathera ®) is a form of peptide receptor radionuclide therapy (PRRT) that has shown efficacy in the treatment of neuroendocrine tumors through its action on somatostatin receptor 2. The effects of Lutathera on endocrine function in metastatic pheochromocytoma and paraganglioma (PPGL) has not been evaluated. Methods: We performed a prospective analysis on 21 patients (10 female, 11 male) with metastatic PPGL receiving (177)Lu DOTATATE (NCT03206060) at our center from July 2017 to August 2019. Hormonal evaluation was obtained 24 and 48 hours after each (177)Lu DOTATATE administration and 4 weeks ± 1 week after each cycle to assess for biochemical endocrine abnormalities (BEAs). Blood samples were obtained after 30 minutes of resting with an in-dwelling intravenous catheter. We excluded BEAs that were present either prior to the initiation of (177)Lu DOTATATE or due to a pre-existing endocrine disorder. Results: We observed BEAs in 18 of 21 (85.7%, 7 female, 11 male) patients. BEAs most commonly involved the pituitary-adrenal axis [ACTH (N: 5-46 pg/mL): 6/21 (28.5%, 5 high, 1 low); serum cortisol (N: 5-25 mcg/dL): 5/21 (23.8%, 2 high, 3 low)], followed by pituitary-thyroid axis [TSH (N: 0.27-4.2 IU/mL): 6/21 (28.5%, 4 high, 2 low); free thyroxine (N: 0.9-1.7 ng/dL): 2/21 (9%, 0 high, 2 low)], pituitary-gonadal axis [FSH (N: 1-11 U/L): 2/21 (9%, 1 high, 1 low); LH (1-8 U/L): 1/21 (5%, 0 high, 1 low); total testosterone (N: 262-1593 ng/dL): 4/21 (19%, 0 high, 4 low)]; and growth hormone [3/21 (N: 0 - 3 ng/mL): (14.3%, 3 high, 0 low)]. Of the 28 observed BEAs, 17/28 (61%) were initially noted during cycle 1, 7/28 (25%) during cycle 2, and 4/28 (14%) during cycle 3, and 16/28 (57%) were noted within 48 hours of (177)Lu DOTATATE injection. There was no significant association between the standardized uptake values of adrenals (p=0.28), pituitary (p=0.75), and thyroid gland (p=0.61) on the baseline diagnostic (68)Ga DOTATATE scan and their respective BEAs. One patient developed overt hypothyroidism and was started on levothyroxine, and another patient developed central adrenal insufficiency likely from immunotherapy started after (177)Lu DOTATATE therapy. In all other patients, BEAs were transient and spontaneously resolved. Limitations included the observational nature of the study, lack of data on levels of IGF-1, parathyroid hormone, or hemoglobin A1C. Conclusion:(177)Lu DOTATATE therapy for metastatic PPGL is associated with biochemical abnormalities in endocrine function. Although mostly transient, there is a potential risk for BEAs to be permanent and to manifest clinically. Therefore, serial monitoring of abnormal hormonal values is necessary and treatment should be considered when appropriate. Studies on larger populations with long-term follow-up are necessary to further investigate the incidence of endocrine abnormalities with (177)Lu DOTATATE therapy.